MOOC and the workplace: key support elements in dig-ital lifelong learning - Robert Farrow (International Entrepreneurship Review, 2018)
This paper examines the relationship between trends in workplace learning and train-ing; the EU policy for lifelong learning; and describes the role that alternative forms of educational delivery such as MOOC can play in supporting future scenarios such as automation and digitalization. The research conducted is based on synthesis of prior research results, literature analysis, qualitative research, specifically course evaluation through roundtable discussion. This paper draws together research into MOOC delivery and impact and contextualises these in relation to both recent workplace trends (digitalisation and automation) and lifelong learning policies within the EU. A conceptual model for differentiating flexible, open and online forms of delivery is introduced.